2020
DOI: 10.1016/j.trecan.2020.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprogression and Immunotherapy: Fact, Fiction, or Alternative Fact?

Abstract: The phenomenon of hyperprogressive disease (HPD) is a provocative phenomenon in the era of immune checkpoint inhibitors (ICI). Multiple groups report HPD in a variety of cancers treated with ICI and it to be associated with shorter progression free survival and overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 25 publications
2
88
1
1
Order By: Relevance
“…Moreover, besides a complete/partial response, stable disease, and progressive disease, one should be aware of two additional patterns of tumor response when using immunotherapy, namely: pseudoprogression (i.e., apparent increase in the tumor burden initially, followed by delayed tumor shrinkage, which could lead to the premature cessation of effective immunotherapy) [ 20 , 21 ] and hyperprogressive disease (i.e., accelerated tumor progression following the introduction of ICIs) [ 22 , 23 ]. Hyperprogressive disease was shown to be associated with older age—in a study including 131 patients treated with anti-PD-1/PD-L1 therapy, 7 out of 36 patients ≥65 years old (19%) were classified as having hyperprogressive disease, compared with 5 out of the 95 patients ≤64 years old (5%), p = 0.01, of which only one patient was <55 years old [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, besides a complete/partial response, stable disease, and progressive disease, one should be aware of two additional patterns of tumor response when using immunotherapy, namely: pseudoprogression (i.e., apparent increase in the tumor burden initially, followed by delayed tumor shrinkage, which could lead to the premature cessation of effective immunotherapy) [ 20 , 21 ] and hyperprogressive disease (i.e., accelerated tumor progression following the introduction of ICIs) [ 22 , 23 ]. Hyperprogressive disease was shown to be associated with older age—in a study including 131 patients treated with anti-PD-1/PD-L1 therapy, 7 out of 36 patients ≥65 years old (19%) were classified as having hyperprogressive disease, compared with 5 out of the 95 patients ≤64 years old (5%), p = 0.01, of which only one patient was <55 years old [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest for the first time, to our knowledge, that some patients who do not respond early to platinum-based chemotherapy are at higher risk for the development of HPD upon immunotherapy. ICIs may promote tumor growth kinetics in certain patients and lead to the development of HPD, with an incidence ranging from 4 to 29% in different studies [21,28] There is no uniform definition for HPD, even though some authors still doubt its existence because it is an ad-hoc observation, and may reflect the natural history of disease [29,30]. The majority of researchers rely upon the rate of target lesion growth to define HPD [21,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…PTEN alterations have also been associated with lower ORR and shorter progression‐free survival (PFS) independently of clinical factors and PD‐L1 status in triple‐negative breast cancer (TNBC) patients treated with ICPI 19 . In addition, studies have indicated that the MDM2 proto‐oncogene, a negative regulator of the TP53 gene, when amplified as seen in multiple tumors, may be associated with disease hyperprogression in patients treated with PD‐1/PD‐L1 inhibitors 20 …”
Section: Introductionmentioning
confidence: 99%